1998
DOI: 10.1002/(sici)1096-911x(199812)31:6<498::aid-mpo6>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carcinoma in childhood and adolescence

Abstract: Background This study reviews the authors' experience from 1979 through 1996 in the management and outcome of 56 patients with nasopharyngeal carcinoma who were under 20 years of age. Procedure There were 33 males and 23 females, their ages ranging from 7 to 19 years (median: 16 years). Forty patients had World Health Organization type III carcinomas, 16 had T4 tumors, 41 had metastatic cervical lymph nodes, and 50 were at stage III or stage IV. Thirty‐two patients were treated with radiation therapy alone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 53 publications
2
10
1
1
Order By: Relevance
“…NPC and in particular undifferentiated NPC is known to be a very radiosensitive tumor [4], thus the main treatment strategy for all the cases of locoregional NPC has been high-dose radiotherapy to the nasopharynx and involved lymph nodes of the neck, and a moderate dose of radiation to uninvolved nodes and surrounding tissue. Concerning radiation's dose, doses greater than 65 Gy have been shown to yield a better local control in a few studies [11,18,19], but other reports have not shown any correlation between the dose of radiation, rate of local relapse, and survival time [20][21][22]. Currently, the optimum dose for a secure control of NPC in children is not yet established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPC and in particular undifferentiated NPC is known to be a very radiosensitive tumor [4], thus the main treatment strategy for all the cases of locoregional NPC has been high-dose radiotherapy to the nasopharynx and involved lymph nodes of the neck, and a moderate dose of radiation to uninvolved nodes and surrounding tissue. Concerning radiation's dose, doses greater than 65 Gy have been shown to yield a better local control in a few studies [11,18,19], but other reports have not shown any correlation between the dose of radiation, rate of local relapse, and survival time [20][21][22]. Currently, the optimum dose for a secure control of NPC in children is not yet established.…”
Section: Discussionmentioning
confidence: 99%
“…Most relapses occur within the first 2 years (median of 8 months) and more than 50 % of patients who relapse have overt distant metastases [11,18,25]. With exclusive radiotherapy, the 5-year survival rate has been reported as 20-60 % in most series of young patients affected by NPC [18,19,26,27]. However, unlike other head and neck carcinomas, NPC is very chemosensitive, and chemotherapy (CHT) can help to reduce tumor burden, improve local control, and eliminate systemic micrometastases.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all of the series were retrospective analyses, with small numbers of patients who were assessed for long periods and were treated on different schedules 10,11,[23][24][25][26] For many years, radiotherapy was the mainstream of treatment for patients with these tumors. However, locoregional and distant control rates are poor.…”
Section: Discussionmentioning
confidence: 99%
“…29 -34 However, more recent publications have shown reasonable local and distant disease control rates in adults and children. 24,25,[35][36][37][38][39][40][41][42][43][44] There are no randomized trials in nasopharyngeal carcinoma in childhood; however, it is interesting to consider three prospective trials: Gasparini et al 37 treated 12 children with advanced nasopharyngeal carcinoma with preradiation chemotherapy and achieved a 75% actuarial 3-year continuous recurrence-free survival rate. Ghim et al 42 reported on a 20-year experience treating children with nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Serin ve arkadaşları da 56 pediatrik NFK hastasını dahil ettikleri çalışmada kemoterapinin radyoterapiye eklenmesiyle sistemik başarısızlık oranının azaldığını bulmuşlardır 18 . Küpeli ve arkadaşlarının 84 hastalık pediatrik NFK serisinde sisplatin bazlı kemoterapi kombinasyonuyla sağkalımın % 80'lere çıktığı rapor edilmiştir 19 .…”
Section: Kemoterapiunclassified